International Trade / New Patterns of Trade, Production and Investment - Grimwade Nigel (Rouledge, 1989)
Introduction, Basic Theories of International Trade and Production, The Changing Structure of World Output and World Trade, Intra-Industry Trade and Specialization, The Rise of the Multinational Corporations and Intra-Firm Trade, New Forms of International Economic Involvement, The Growth of Japan and the Emergence of the Newly-Industrializing Countries, The Growth of the New Protectionism and the Adjustment Problem, Trade in Services, References, Glossary, Index.